Parathenar pattern in man and in other primates - Wojciechowska, Halina (Anthropological Review, 1979)
The palmar area of the human hand situated between thenar and hypothenarwas called by Cummins and Midlo parathenar area and the pattern on it — parathenar pattern. Morphological relationship of this pattern to the hypothenar area is not certain. The frequencies of parathenar palmar pattern are: 0,3 - 0,4%. Recently it has been reported that frequency of parathenar palmar pattern increases in individuals with congenital heart diseases. The presence of parathenar palmarpattern and parathenar plantar pattern was also determined in some groups of monkeys. Since there is still no information about the presence of the parathenarplantar pattern on the human soles, the association of the parathenar pattern with prehension seems to be evident. The position and type of the pattern in otherprimates allows us to suggest that parathenar pattern is connected with central, volar pad rather than with pad of the hypothenar.